Bachelors of a different sort : Queer aesthetics, material culture and the modern interior in Britain - Potvin, John (Book collections on Project MUSE., 2015)
This title considers the complicated relationships between the modern queer bachelor and interior design, material culture and aesthetics in Britainbetween 1885 and 1957.